A comparative study of service-oriented architecture maturity model - Hamzah, Mohd Hamdi Irwan; Baharom, Fauziah; Mohd, Haslina (2016)
Service-oriented Architecture (SOA) maturity model is a benchmark for evaluating and assessing the maturity of SOA adoption. Several of SOA maturity models have been constructed by the academia and industry.However, these models contradict with each other in determining “what” need to be assessed in SOA adoption.Therefore, the aims of this study is to review and compare the existing SOA maturity models that were commonly referred such as SOAMM, SIMM, CSOAMM, Inaganti’s Model, iSOAMM, Welke’s Model and SOASMM in order to determine which model should be enhanced to reflect the true definition of SOA. The findings implies that the existing models have their own strengths and weaknesses and based on these findings, this study identify that Welke’s model is the most suitable model that should be enhanced. This study has successfully analyze the existing models and identify an issue that deserve future investigation such as the need to provide two dimensional evaluations for both IT benefits and business benefits and the need to improve the evaluation processes in the SOA maturity model.